Comprehensive analytical model for polarization curve of a PEM fuel cell and experimental validation - Thosar, Aniket U.; Agarwal, Harshal; Govarthan, S.; Lele, Ashish K. (Chemical Engineering Science, 2019)
The kinetics of cathodic oxygen reduction reaction (ORR) in a proton exchange membrane fuel cell (PEMFC) is significantly modulated by the resistances for transport of reactants to the catalytic sites offered by different components of the fuel cell. This modulation governs the polarization curve of the PEMFC. Consequently, the various operating, geometric and material parameters of the fuel cell dictate the polarization curve. The effects of these parameters on the polarization curve over the entire range of current density, from zero to limiting current, can be predicted using detailed numerical simulations, which are however expensive. Analytical models, although simple can capture the essential details of physico-chemical processes occurring inside a PEMFC and are significantly inexpensive. In this article, we derive an analytical equation of the polarization curve which is valid over the entire range of current density. Specifically, the representative situation of a humidified low temperature PEMFC is considered wherein oxygen transport resistance in the cathode catalyst layer (CCL) is encountered at lower current density than proton transport resistance in the CCL. A novel experimental methodology is illustrated to confirm that this is indeed the case. Next, we elucidate a procedure to determine in-situ oxygen diffusion coefficients in the various domains of an operational PEMFC. Finally, it is shown that the analytical polarization curve predicted using these parameters is in excellent agreement with the experimental and numerically simulated polarization curves over the entire range of current density. The significance of this work is that the analytical model relates the performance of a PEMFC to all operating and geometric parameters as well as the average transport and kinetic properties of the materials used in its different components, without the need for computationally expensive numerical simulations. The model can therefore provide useful insights for enhancing the performance of PEMFC in different regimes of current density as well as for diagnostic purposes. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Fuel cell equation; Modelling; PEMFC; Polarization curve

Interdigitated flow field impact on mass transport and electrochemical reaction in high-temperature polymer electrolyte fuel cell - Agarwal, Harshal; Thosar, Aniket U.; Bhat, Santoshkumar D.; Lele, Ashish K. (Journal of Power Sources, 2022)
The enhanced performance of Polybenzimidazole (PBI) based high-temperature polymer electrolyte fuel cell (HT-PEFC) with interdigitated flow field over the other flow fields can be a consequence of higher average pressure developed on the flow field due to dead end in the channels or faster mass transport due to pressuredriven convection in the gas diffusion layer (GDL). In the present study, the effect of average pressure on the flow field and mass transport mechanism in the GDL on the HT-PEFC performance have been systematically decoupled. Three-dimensional simulation validated by experimental studies confirm that the enhanced performance in case of the interdigitated flow field is due to faster mass transport in the GDL and not due to higher average gas pressure. The simulation studies are performed on the interdigitated flow field and compared against the parallel flow field to have an insight into the effect of key operating and geometric parameters. There exists an optimum value for channel to rib ratio and current density saturates after an air stoichiometry of 4 which is validated by experiments.
Keywords: HT-PEFC; Interdigitated flow field; Mass transport mechanism; pressure; stoichiometry